(untitled) (Interapia – Journal of Clinic, Culture and Mental Sciences, 2025)
Abstract The article critically examines Freud’s theory of penis envy from a gender perspective, emphasizing Karen Horney’s contributions and the need for a more inclusive psychoanalytic interpretation of female subjectivity.